2020
DOI: 10.1101/2020.07.30.20164970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High SARS-CoV-2 seroprevalence in Health Care Workers but relatively low numbers of deaths in urban Malawi

Abstract: Background In low-income countries, like Malawi, important public health measures including social distancing or a lockdown, have been challenging to implement owing to socioeconomic constraints, leading to predictions that the COVID-19 pandemic would progress rapidly. However, due to limited capacity to test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, there are no reliable estimates of the true burden of infection and death. We, therefore, conducted a SARS-CoV-2 serosurvey amo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
95
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 12 publications
14
95
2
Order By: Relevance
“…These SSA countries issued national guidelines on recommended safety measures, initiated immediate contact tracing, prevented mass gatherings, instituted national lockdown and curfew, closed schools and urged the private sector and the government personnel to work from home. It was noted that Zambia, which did not fully implement the interventions described in this study as well as other countries not included in our review that have struggled to put into action public health interventions 107 , 108 , reported no significant increases in deaths compared to countries with more robust responses reported here. There, consistent with the recent study by M. Njenga et al .…”
Section: Resultsmentioning
confidence: 63%
“…These SSA countries issued national guidelines on recommended safety measures, initiated immediate contact tracing, prevented mass gatherings, instituted national lockdown and curfew, closed schools and urged the private sector and the government personnel to work from home. It was noted that Zambia, which did not fully implement the interventions described in this study as well as other countries not included in our review that have struggled to put into action public health interventions 107 , 108 , reported no significant increases in deaths compared to countries with more robust responses reported here. There, consistent with the recent study by M. Njenga et al .…”
Section: Resultsmentioning
confidence: 63%
“…Mean age of HCWs ranged from 31.2 [ 51 ] years to 47.9 years [ 57 ], while sample size ranged from 25 [ 40 ] to 40,329 HCWs [ 14 ]. Regarding the study design, 26 studies were cross-sectional studies [ 14 , 15 , 18 , 19 , 21 , [23] , [24] , [25] , [27] , [28] , [29] , [30] , [31] , [32] , [34] , [35] , [36] , [37] , 39 , 44 , 47 , 52 , 54 , 58 , 60 , 61 ], 20 studies were prevalence studies [ 17 , 26 , 33 , 38 , [40] , [41] , [42] , [43] , 45 , 46 , [48] , [49] , [50] , [51] , 53 , 55 , 56 , 57 , 59 , 62 ], and three studies were cohort studies [ 16 , 20 , 22 ]. All studies except one [ 31 ] used a convenience sample, while response rate ranged from 47.7% [ 19 ] to 100% [ 36 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies except one [ 31 ] used a convenience sample, while response rate ranged from 47.7% [ 19 ] to 100% [ 36 , 60 ]. Forty-two studies were conducted in hospitals [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ], four studies in primary care facilities and hospitals [ 14 , 25 , 28 , 49 ], two studies in primary care facilities [ 35 , 62 ] and one study in cancer centers [ 59 ]. Thirty-five studies were published in journals [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , <...>…”
Section: Resultsmentioning
confidence: 99%
“…Further areas of use could be large-scale seroprevalence studies in low-and middle-income countries[28] without sufficient in-country laboratory capacity by sending specimens by international mail. Especially in the current SARS-CoV-2 pandemic, population-based seroprevalence studies could elucidate some urgent questions such as the impact of COVID-19 in Africa[29].New technology and method developments such as those reported here will make it possible to overcome the current centralized molecular diagnostics paradigm, which is focused on hospitals and point of care settings rather than on patients and individuals seeking simple, affordable, and convenient molecular…”
mentioning
confidence: 99%